2021
DOI: 10.3389/fphys.2021.682711
|View full text |Cite
|
Sign up to set email alerts
|

Lateral Preoptic Area Neurons Activated by Angiotensin-(1–7) Increase Intravesical Pressure: A Novel Feature in Central Micturition Control

Abstract: Central micturition control and urine storage involve a multisynaptic neuronal circuit for the efferent control of the urinary bladder. Electrical stimulation of the lateral preoptic area (LPA) at the level of the decussation of the anterior commissure in cats evokes relaxation of the bladder, whereas ventral stimulation of LPA evokes vigorous contraction. Endogenous Angiotensin-(1–7) [(Ang-(1–7)] synthesis depends on ACE-2, and its actions on binding to Mas receptors, which were found in LPA neurons. We aimed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…On the other hand, another hypothesis is that Ang-(1–7) infused intravenously could also act centrally in the lateral preoptic area and bind to the Mas receptors of this area. Previous report has shown that Ang-(1–7) injected into the lateral preoptic area increases IP with a latency for the response of approximately 10 min and achieves a peak response approximately 25 min after injection without inducing any changes in RC and arterial pressure ( Lamy et al, 2021 ). Hence, the response observed with Ang-(1–7) infused intravenously in the current study could be dependent on direct action on the UB and/or be due to an action at the intrarenal level and/or through activation of Mas receptors in the lateral preoptic area.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…On the other hand, another hypothesis is that Ang-(1–7) infused intravenously could also act centrally in the lateral preoptic area and bind to the Mas receptors of this area. Previous report has shown that Ang-(1–7) injected into the lateral preoptic area increases IP with a latency for the response of approximately 10 min and achieves a peak response approximately 25 min after injection without inducing any changes in RC and arterial pressure ( Lamy et al, 2021 ). Hence, the response observed with Ang-(1–7) infused intravenously in the current study could be dependent on direct action on the UB and/or be due to an action at the intrarenal level and/or through activation of Mas receptors in the lateral preoptic area.…”
Section: Discussionmentioning
confidence: 99%
“…The Image Lab software TM (Bio-rad) was used to quantify the densitometry of the blot containing the corresponding protein of interest. The optical density (OD) of Mas receptors and ACE-2 was normalized by the expression of total protein, as described in a previous study by Lamy et al (2021) .…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations